METHODOLOGICAL ASPECTS OF THE INTERNAL CONTROL SYSTEM FORMATION - Larisa I. Egorova; Elizaveta S. Sokolova; Galina V. Shadrina (Статистика и экономика, 2016)
The methodological aspects of the internal control system formation are stated in the article. The great attention is focused on the problems of financial statements misrepresentation. The basic principles and structure of the internal control system are discussed in this article.